Numerical analysis of pump-signal-direction effect on the performance of EDFA systems. Issue 4 (21st November 2019) - Parali, Ufuk; Pinar, Cahit
Abstract : Purpose: The purpose of this study is to develop new tandem configurations of erbium-doped fiber amplifier (EDFA) using all possible pump-signal-direction schemes in simulation to identify a system configuration with the best performance in the means of the highest gain with the lowest noise figure (NF) output. Design/methodology/approach: The spatial evolution of the physical properties such as gain, NF, population density and amplified spontaneous emission along the total length of the double-stage single-pass EDFA and single-stage double-pass EDFA configurations under all possible pumping direction schemes was investigated. Giles and Desurvire method was used for the mathematical modeling of these configurations where the two level coupled system model equations was solved in MATLAB. In the simulation of the all proposed configurations, an input signal of −35 dBm at the wavelength of 1550 nm and a total of 14 mW pump power at the wavelength of 1480 nm was used for a consistent analysis. Findings: The numerical value of the results obtained is specific to the input parameter values used in the simulations; however, configuration-wise, the EDFA systems found with the best performance are not parameter specific. Originality/value: The results of this numerical work will help future experimental research of designing and developing ultra-efficient EDFA systems.